1985
DOI: 10.2307/2408363
|View full text |Cite
|
Sign up to set email alerts
|

On the Evolution of Pseudogamy

Abstract: A. density- and frequency-dependent model for the evolution and maintenance of pseudogamous females is developed and analyzed. Ecological as well as evolutionary aspects of pseudogamy are discussed. Criteria are described for the stable coexistence of sexual females and pseudogamous females under natural conditions. The conditions for invasion of a normal bisexual population by pseudogamous females are less stringent than the conditions for stable coexistence. Hence, we expect that some populations will be cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 22 publications
1
28
1
Order By: Relevance
“…This question has been addressed in another poeciliid, Poeciliopsis, where several studies demonstrated that mating success of asexuals was inversely correlated with density (e.g. Moore & McKay 1971;Stenseth et al 1985; but see Keegan-Rogers & Schultz 1988). Our data, however, do not support negative frequency dependence of male mate choice, since P. formosa was always the more common species.…”
Section: Discussioncontrasting
confidence: 69%
“…This question has been addressed in another poeciliid, Poeciliopsis, where several studies demonstrated that mating success of asexuals was inversely correlated with density (e.g. Moore & McKay 1971;Stenseth et al 1985; but see Keegan-Rogers & Schultz 1988). Our data, however, do not support negative frequency dependence of male mate choice, since P. formosa was always the more common species.…”
Section: Discussioncontrasting
confidence: 69%
“…For example, coexistence ofan asexual sperm parasite and its sexual host (such as occurs in Poeciliopsisi does not require niche partitioning (Moore and McKay, 1971;Keister et al, 1981;Moore, 1976;Stenseth et al, 1985). However, sperm-dependence alone does not explain coexistence of multiple clones, and it has no bearing on coexistence among clones of a truly parthenogenetic species.…”
Section: Discussionmentioning
confidence: 99%
“…One possible factor is negative frequency-dependent reproductive success of P. formosa (Moore 1984;Stenseth et al 1985;Kirkendall and Stenseth 1990;Ryan et al 1996) as a result of plastic or context-dependent male mate choice (Moore 1984;Keenan-Rogers and Schultz 1988). Avoidance of P. formosa may be more important when the cost of mating with a gynogenetic female is a loss of a rare opportunity to mate with a conspecific female (Kawecki 1988;Pfennig 1998).…”
Section: What Of the Evolutionary Fate Of Amazon Mollies?mentioning
confidence: 99%